PRAKTIK INVESTASI SUKUK PADA CV. MANUNGGAL SEHATI MAGETAN PERSPEKTIF HUKUM EKONOMI SYARI’AH - Syihan Ali Ahmad; Ninik Azizah (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to examine the practice of sukuk investment at CV. Manunggal Sehati Magetan which is located on Jl. Village No.27, Krajan, Mantren, Kec. Karangrejo, Magetan Regency based on a sharia economic law perspective. The research method used is the Empirical Juridical method, with a conceptual and phenomenological approach. Using Inductive and Descriptive analysis techniques. The data collection techniques used are observation, interviews, documentation, questionnaires and library data. The research results show that CV Sukuk investment practices. Manunggal Sehati Magetan uses 2 investment systems, namely investments above 500,000,000 (five hundred million rupiah) by providing ijarah objects or collateral, investments below 500,000,000 (five hundred million rupiah) by using a profit sharing system without any collateral or ijarah objects . make the agreement valid according to the principles of agreement on freedom of belief. However, when the sukuk investment is issued above 500 million and cash, especially not through a government SPV, this makes the contract also flawed. Meanwhile, the investment system under 500,000,000 million in drafting the agreement does not involve investors or the investors' guardians, making the agreement void or in fasakh according to the principles of agreement on freedom of contract and included in standard clauses.